Chemical Constituents and Biological Activity of Kaempferia Angustifolia, K. Rotunda,Spermacoce Articularis and S. Exilis - Neoh, Bee Keat (2006)
Kaempferia angustifolia, K rotunda (Zingiberaceae), Spennacoce articularis and S. exilis (Rubiaceae) were chosen since they have long been used traditionally in medicinal treatment. In this research, isolation and separation work had been carried out using various solvents and chromatographic methods. The structure of these compounds were determined by using spectroscopic methods such as ineared (IR), nuclear magnetic resonance ('H, 13C and 2D- NMR), mass spectrometry (MS) and by comparison with the data reported previously. The crude extracts and some of the isolated compounds were subjected to the biological activity test: antioxidant, antimicrobial tests, cytotoxic screening and larvicidal activity.Extracts fiom Kaempferia angush~oliah ave yielded a new compound angustifolienol (58), together with seven other compounds; crotepoxide (33), p-sitosterol (a), boesenboxide (M), 2'-hydroxy-4, 4', 6'-trimethoxychalcone (Xi), 6-methylzeylenol (59), and sucrose (60), and zeylenol(35). Frationation of extracts fiom K. rotunda has yielded five pure compounds; crotepoxide (33), tetracosanoic acid (61), benzoic acid (62), stigmasterol (45) and p-sitosterol (44). Both tetracosanoic acid (61) and benzoic acid (62) are new to species. Extracts fiom S. art'iculm's gave two pure compounds, identified as ursolic acid (63) and stigmasterol (45). While the extracts from S. exilis gave four compounds, benzo[g]isoquinoline-5,IOdione (64), stigmasterol (49, hexadecanoic acid (65) and ursolic acid (63). Phytochemical studies on later species had never been reported before. Acetylations of new compound, angustifolienol (58) gave two derivatives, triacetoxyangustifolienol (66) and diacetoxyangustifolienol (67). Both are new compounds, and have never been reported previously either as natural product or synthesized compounds. The major constituents of the essential oil of K. angustifolia was DL- camphor (20.57